A humanised tissue‐engineered bone model allows species‐specific breast cancer‐related bone metastasis in vivo. (29th November 2017) - Quent, VMC; Taubenberger, AV; Reichert, JC; Martine, LC; Clements, JA; Hutmacher, DW; Loessner, D
Abstract: Bone metastases frequently occur in the advanced stages of breast cancer. At this stage, the disease is deemed incurable. To date, the mechanisms of breast cancer‐related metastasis to bone are poorly understood. This may be attributed to the lack of appropriate animal models to investigate the complex cancer cell–bone interactions. In this study, two established tissue‐engineered bone constructs (TEBCs) were applied to a breast cancer‐related metastasis model. A cylindrical medical‐grade polycaprolactone‐tricalcium phosphate scaffold produced by fused deposition modelling (scaffold 1) was compared with a tubular calcium phosphate‐coated polycaprolactone scaffold fabricated by solution electrospinning (scaffold 2) for their potential to generate ectopic humanised bone in NOD/SCID mice. While scaffold 1 was found not suitable to generate a sufficient amount of ectopic bone tissue due to poor ectopic integration, scaffold 2 showed excellent integration into the host tissue, leading to bone formation. To mimic breast cancer cell colonisation to the bone, MDA‐MB‐231, SUM1315, and MDA‐MB‐231BO breast cancer cells were cultured in polyethylene glycol‐based hydrogels and implanted adjacent to the TEBCs. Histological analysis indicated that the breast cancer cells induced an osteoclastic reaction in the TEBCs, demonstrating analogies to breast cancer‐related bone metastasis seen in patients.